INITIAL AND PROSPECTIVE FORMS OF KINDERGARTEN-FAMILY COOPERATION AS AN IMPORTANT FACTOR IN THE COMPREHENSIVE DEVELOPMENT OF PRESCHOOLERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article explores the significance of collaboration between kindergartens and families in fostering the comprehensive development of preschool children. It examines initial forms of cooperation, such as parent meetings, consultations, and parental involvement in educational activities. Furthermore, it analyzes prospective directions, including digitalization of interaction, individualization of educational processes, development of family participation formats, and provision of psychological and pedagogical support to parents. The author emphasizes the importance of aligning educational approaches to ensure the harmonious development of the child, highlighting the necessity of creating a unified educational environment that integrates the efforts of educators and families.